Three-tiered support: Individual, school and institution-wide initiatives through a first year advisor network through a first year advisor network - Helen Kemp; Ann Lefroy; Natalie Callan (International Journal of the First Year in Higher Education, 2013)
The First Year Advisor Network (FYAN) at Murdoch University has a three-tiered approach offering (i) individual, (ii) school-based and (iii) institution-wide student access to support that addresses the diverse needs of the contemporary student population. The programs, campaigns and open-door policy of the FYAN, along with the unique structure of the network, have been developed to provide these varied points of access to student support. Importantly, First Year Advisors (FYAs) act as a generalised support for all students and as a hub to accessing specialised support at the University. This paper highlights the range of initiatives developed by the FYAN and emphasises that while outreach contact is a successful way to promote access to support, many students still self identify as at-risk and will access FYAs for direct and referral advice.